2001
DOI: 10.1021/ma001505c
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Enzymatic Degradation Behavior of Poly[(R)-3-hydroxybutyrate] Lamellar Single Crystals by Atomic Force Microscopy

Abstract: The enzymatic degradation behavior of solution-grown single crystals of poly[(R)-3hydroxybutyrate] (P(3HB)), which were adsorbed on the surface of highly ordered pyrolytic graphite, with an extracellular PHB depolymerase from Alcaligenes faecalis T1 was directly observed by atomic force microscopy. At the initial stage of degradation, enzymatic action of both adsorption and hydrolysis produced smaller crystal blocks by predominant degradation of distorted regions of a single crystal. Subsequently, the hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 29 publications
5
66
0
Order By: Relevance
“…[19] The degradation pathway can be explained by a loosely chain packing region along the long axis of crystal, that is, a linear switchboard region with a random reentry fold.…”
Section: Enzymatic Degradation Behaviors and Plausible Structures Of mentioning
confidence: 99%
“…[19] The degradation pathway can be explained by a loosely chain packing region along the long axis of crystal, that is, a linear switchboard region with a random reentry fold.…”
Section: Enzymatic Degradation Behaviors and Plausible Structures Of mentioning
confidence: 99%
“…Enzymatic degradation of PHB single crystals with PHB depolymerases from Pseudomonas lemoignei (Nobes et al 1996) and R. pickettii T1 (Iwata et al 1997b;Murase et al 2001a) was observed with the transmission electron microscope and the atomic force microscope. These studies demonstrated that enzymatic hydrolysis progresses from the short ends of the lath-like-shaped PHB lamellar single crystals to form cracks along the long axis.…”
Section: Structure and Degradation Of Phb And Copolymersmentioning
confidence: 99%
“…Accordingly, the slit was generated by the degradation of less-ordered region in the lamellar crystal along the crystallographic a-axis. [19,20] As the degradation proceeded, the lamellar crystal revealed a splintered morphology at the tip of lamellar crystal (at area (f) in Figure 3G). After that, the splintered lamellar crystal was degraded and disappeared (at area (g) in Figure 3H).…”
Section: Direct Observation Of Enzymatic Degradation Processmentioning
confidence: 99%
“…[1][2][3][4][5] PHA materials can be hydrolyzed by specific microbial enzymes of extracellular poly(hydroxybutyrate) (PHB) depolymerases of microorganisms isolated from various environments. [6][7][8][9][10] To elucidate the mechanism of enzymatic hydrolysis of PHA materials with a PHB depolymerase, the enzymatic reaction has been investigated using single crystals [11][12][13][14][15][16][17][18][19][20] and films. [21][22][23][24][25][26][27][28][29][30][31] These reported results have indicated that the rates of enzymatic erosion for PHA materials are affected by both the chemical structure of monomeric units and the solid-state structure of samples.…”
Section: Introductionmentioning
confidence: 99%